Conditional Activation of NF‐κB Inducing Kinase (NIK) in the Osteolineage Enhances Both Basal and Loading‐Induced Bone Formation. (31st July 2019) - Davis, Jennifer L; Cox, Linda; Shao, Christine; Lyu, Cheng; Liu, Shaopeng; Aurora, Rajeev; Veis, Deborah J
ABSTRACT: Studies from global loss‐of‐function mutants suggest that alternative NF‐κB downstream of NF‐κB inducing kinase (NIK) is a cell‐intrinsic negative regulator of osteogenesis. However, the interpretation of the osteoblast and/or osteocyte contribution to the bone phenotype is complicated by simultaneous osteoclast defects in these models. Therefore, we turned to a transgenic mouse model to investigate the direct role of NIK in the osteolineage. Osx‐Cre;NT3 animals ( NT3‐Cre + ), which bear a constitutively active NIK allele ( NT3 ) driven by Osx‐Cre, were compared with their Cre ‐negative, Control ( Ctrl ) littermates. NT3‐Cre +  mice had elevated serum P1NP and CTX levels. Despite this high turnover state, µCT showed that constitutive activation of NIK resulted in a net increase in basal bone mass in both cortical and cancellous compartments. Furthermore, NT3‐Cre +  mice exhibited a greater anabolic response following mechanical loading compared with controls. We next performed RNA‐Seq on nonloaded and loaded tibias to elucidate possible mechanisms underlying the increased bone anabolism seen in NT3‐Cre +  mice. Hierarchical clustering revealed two main transcriptional programs: one loading‐responsive and the other NT3 transgene‐driven. Gene ontology (GO) analysis indicated a distinct upregulation of receptor, kinase, and growth factor activities including Wnts, as well as a calcium‐response signature in NT3‐Cre +  limbs. The promoters of these GO‐term associated genes, including many known to be bone‐anabolic, were highly enriched for multiple κB recognition elements (κB‐RE) relative to the background frequency in the genome. The loading response in NT3‐Cre +  mice substantially overlapped (>90%) with Ctrl . Surprisingly, control animals had 10‐fold more DEGs in response to loading. However, most top DEGs shared between genotypes had a high incidence of multiple κB‐RE in their promoters. Therefore, both transcriptional programs (loading‐responsive and NT3 transgene‐driven) are modulated by NF‐κB. Our studies uncover a previously unrecognized role for NF‐κB in the promotion of both basal and mechanically stimulated bone formation. © 2019 American Society for Bone and Mineral Research.